Transition metal nickel prevents Tau aggregation in Alzheimer's disease - Gorantla, Nalini Vijay; Das, Rashmi; Balaraman, Ekambaram; Chinnathambi, Subashchandrabose (International Journal of Biological Macromolecules, 2020)
Alzheimer's disease is the leading cause of dementia, effecting majority of aged people worldwide. The multifaceted effectors of Alzheimer's disease primarily include Tau, amyloid-beta along with hyper activation of kinases, oxidative stress and mutations etc., makes it challenging to design therapeutics. Tau is a microtubule-associating protein, which is subjected to cellular stress resulting in the formation of neurofibrillary tangles, leading to loss of affinity for microtubules. This causes loss of microtubule stability and in turn alters axonal integrity. In the present work, emphasis towards understanding interaction of nickel with Tau was made. Metals such as iron, zinc, copper and lead etc., are known to modulate Tau conformation and enhance its aggregation. Our results showed the deliverance of Tau aggregation by nickel and its synthetic morpholine conjugate. Nickel prevents aggregation by inducing degradation of Tau as evidenced by SDS-PAGE and TEM. Nickel and the synthetic conjugate being non toxic to neuro2a cells and prevent Tau aggregation, might direct these complexes to overcome AD. (C) 2019 Published by Elsevier B.V.
Keywords: Aggregation; Alzheimer's disease; metals; Morpholine; Nickel chloride; Tau

Tau aggregates improve the Purinergic receptor P2Y12-associated podosome rearrangements in microglial cells - Chinnathambi, Subashchandrabose; Das, Rashmi; Desale, Smita Eknath (Biochimica Et Biophysica Acta-Molecular Cell Research, 2023)
Alzheimer's disease (AD) is a progressive neurodegenerative disease that is associated with protein misfolding, plaque accumulation, neuronal dysfunction, synaptic loss, and cognitive decline. The pathological cascade of AD includes the intracellular Tau hyperphosphorylation and its subsequent aggregation, extracellular Amyloid-& beta; plaque formation and microglia-mediated neuroinflammation. The extracellular release of aggregated Tau is sensed by surveilling microglia through the involvement of various cell surface receptors. Among all, purinergic P2Y12R signaling is involved in microglial chemotaxis towards the damaged neurons. Microglial migration is highly linked with membrane-associated actin remodeling leading to the phagocytosis of extracellular Tau species. Here, we studied the formation of various actin structures such as podosome, lamellipodia and filopodia, in response to extracellular Tau monomers and aggregates. Microglial podosomes are colocalized with actin nucleator protein WASP, Arp2 and TKS5 adaptor protein during Tau-mediated migration. Moreover, the P2Y12 receptors were associated with F-actin-rich podosome structures, which signify the potential of Tau aggregates in microglial chemotaxis through the involvement of actin remodeling.
Keywords: Alzheimer `s disease; Filopodia; microglia; Podosome; Tau aggregates